The Role of Jordanian Financial Institutions’ in Supporting Entrepreneurial Success and Cope Up the Challenges (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Current study investigates the role of Jordanian financial institutions for supporting entrepreneurial success in the country. For this purpose, the study focuses on various tools implemented by Jordanian banks listed on Amman stock exchange to highlight their contribution in supporting entrepreneurs starting their work and attaining SDG (sustainable development goals). The study reports different documents and academic literature for determining various types of financing instruments offered by financial institutions for sustainable development of entrepreneurs. Moreover, instruments, financial policies and financial services of Jordanian banks are reviewed that offer support to entrepreneurs. The study also reports various types of challenges faced by entrepreneurs. It also highlights the role of relationship among financial institutions and other agencies in providing financial support to Jordanian entrepreneurs in different economic sectors.